Reactions to the Law by Minority Religions - Barker, Eileen (Routledge Inform Series on Minority Religions and Spiritual Movements Ser., 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of Figures -- Notes on Contributors -- 1 Fight, Flight or Freeze? Reactions to the Law by Minority Religions -- 2 Stand Up for Your Rights: (Minority) Religions' Reactions to the Law in Estonia -- 3 Jehovah's Witnesses and the Law: "Caesar's things to Caesar, but God's things to God" -- 4 Scientology Behind the Scenes: The Law Changer -- 5 No Stranger to Litigation: Court Cases Involving the Unificationist Church/Family Federation in the United States -- 6 Legal Challenges Posed to the Unificationist Church in Europe: Perspectives from a Unificationist Advocate for Religious Freedom -- 7 The "Doukhobor Problem" in Canada: How a Russian Mystical Sect Responded to Law Enforcement in British Columbia, 1903-2013 -- 8 Making Sense of the Institutional Demarcation: Tenrikyō's Response to Legal Environments in France -- 9 Strategies in Context: The Essenes in France and Canada -- 10 Reactions to Legal Challenges by Aum Shinrikyō and its Successor Organisations -- 11 Religious Persecution and Refugees: Legal and Communication Strategies of the Church of Almighty God in Asylum Cases -- 12 Minority Religion Reactions to the European Court of Human Rights -- 13 Minority Religions Respond to the Law: A Theoretical Excursus -- Index.